2020
DOI: 10.1002/icd.2173
|View full text |Cite
|
Sign up to set email alerts
|

Executive function and screen‐based media use in preschool children

Abstract: The aim of this study was to explore associations between time spent using various media devices and executive abilities in preschoolers. Participants were 190 children (44.2% female; mean age 58.75 months, SD = 7.27). The Shape School, the Missing Scan and the Head and Feet tasks were administered to children to assess three core executive functions (mental set shifting, working memory, and inhibitory control). Parents provided information on the daily time children spent watching television and using smartph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 50 publications
2
30
1
2
Order By: Relevance
“…MST has been validated by Roman et al (2014) as a workable and reliable measure of working memory in preschool children (3–6 years in age). Recently, Jusienė et al (2020) have adopted MST to test 190 preschool children’s working memory and further verified it with sound psychometric properties. Among 65 Beanie Babies (small animal-shaped bean-filled bags), 15 were chosen and used as test stimuli in this study.…”
Section: Methodsmentioning
confidence: 99%
“…MST has been validated by Roman et al (2014) as a workable and reliable measure of working memory in preschool children (3–6 years in age). Recently, Jusienė et al (2020) have adopted MST to test 190 preschool children’s working memory and further verified it with sound psychometric properties. Among 65 Beanie Babies (small animal-shaped bean-filled bags), 15 were chosen and used as test stimuli in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Centre Recruitment: A total of 18 early childhood education and care (ECEC) centers were recruited from the Illawarra region—a coastal region situated immediately south of Sydney, New South Wales, Australia—using a stratified sampling process based on their suburb. Using the area-level socio-economic status (SES) index of the Australian Bureau of Statistics (Socio-Economic Indices for Areas, or SEIFA, Index of Relative Socio-Economic Advantage and Disadvantage; (IRSAD)) [ 32 ], ECEC centers in the region were categorized into low (deciles 1–4), medium (deciles 5–7), or high SES areas (deciles 8–10). The number of ECEC centers invited to participate from each socio-economic group was proportional to the population distribution.…”
Section: Methodsmentioning
confidence: 99%
“…Other articles in this special issue focused on contextual factors beyond the parent–child dyad, including technology, neighbourhood chaos, relationships at school, and the broader cross‐national cultural context. Jusiene, Rakickienė, Breidokiene, and Laurinaitytė () addressed the issue of whether screen time is associated with cognitive function by examining associations between use of various screen‐media devices and EF abilities in a sample of 190 four‐ and five‐year‐old children. Using a cross‐sectional design, the authors found no significant associations between TV, computer, smartphone, or tablet use and inhibitory control, working memory, or cognitive flexibility/shifting in preschoolers.…”
Section: Other Relevant Contextsmentioning
confidence: 99%